Primary and secondary structures of Escherichia coli MRE 600 23S ribosomal RNA. Comparison with models of secondary structure for maize chloroplast 23S rRNA and for large portions of mouse and human 16S mitochondrial rRNAs - Branlant, Christiane (1981)
We determined 90% of the primary structure of E.coli MRE 600 23S rRNA by applying the sequencing gel technique to products of T1, S1, A and Naja oxiana nuclease digestion. Eight cistron heterogeneities were detected, as well as 16 differences with the published sequence of a 23S rRNA gene of an E.coli K12 strain. The positions of 13 post-transcriptionally modified nucleotides and of single-stranded, double-stranded and subunit surface regions of E.coli 23S rRNA were identified. Using these experimental results and by comparing the sequences of E.coli 23S rRNA, maize chloro. 23S rRNA and mouse and human mit 16S rRNAs, we built models of secondary structure for the two 23S rRNAs and for large portions of the two mit rRNAs. The structures proposed for maize chloroplast and E.coli 23S rRNAs are very similar, consisting of 7 domains closed by long-range base-pairings. In the mitochondrial 16S rRNAs, 3 of these domains are strongly reduced in size and have a very different primary structure compared to those of the 23S rRNAs. These domains were previously found to constitute a compact area in the E.coli 50S subunits. The conserved domains do not belong to this area and contain almost all the modified nucleotides. The most highly conserved domain, 2042-2625, is probably part of the ribosomal A site. Finally, our study strongly suggests that in cytoplasmic ribosomes the 3′-end of 5.8S rRNA is basepaired with the 5′-end of 26S rRNA. This confirms the idea that 5.8S RNA is the counterpart of the 5′-terminal region of prokaryotic 23S rRNA.